Pancasila, Islam, and Harmonising Socio-Cultural Conflict in Indonesia - Badrun, Badrun; Sujadi, Sujadi; Warsah, Idi; Muttaqin, Imron; Morganna, Ruly (Al-Jami'ah: Journal of Islamic Studies, 2023)
The compatibility of Islam and Pancasila, the Indonesia’s national philosophy, is still interesting to elaborate even though there have been numerous discussions on the theme. Notably, this paper addresses the harmony of Pancasila and Islam as the umbrella for nationhood and statehood in Indonesia. The writers argue that Pancasila and Islam coexist harmoniously in Indonesia, and this kind of harmony is a valuable esteem to reinforce unity, diversity, and cultural heritage within the society. The acculturation of Pancasila is an effort to integrate its values into daily life through traditions and practices involving various stakeholders. This acculturation will encourage acceptance of diversity and prevent religious extremism. On the other hand, conflicts between political Islam and nationalist groups in Indonesia affect cultural-religious expressions and disrupt harmony. Pancasila is vital in addressing these conflicts and promoting diversity and ongoing dialogues.[Kesesuaian Islam dan Pancasila sebagai falsafah bangsa Indonesia masih menarik untuk dijabarkan meski sudah banyak pembahasan mengenai tema tersebut. Secara khusus, tulisan ini membahas tentang kerukunan Pancasila dan Islam sebagai payung kehidupan berbangsa dan bernegara di Indonesia. Penulis berpendapat bahwa Pancasila dan Islam dapat hidup berdampingan secara harmonis di Indonesia dan keharmonisan tersebut merupakan sebuah penghargaan yang tinggi untuk mempertegas persatuan, keberagaman, dan warisan budaya dalam masyarakat. Pembudayaan Pancasila menjadi upaya untuk mengintegrasikan nilai-nilainya ke dalam kehidupan sehari-hari melalui tradisi dan praktik yang melibatkan berbagai pemangku kepentingan. Akulturasi ini akan mendorong penerimaan keberagaman dan mencegah ekstremisme agama. Di sisi lain, konflik antara politik Islam dan kelompok nasionalis di Indonesia berdampak pada ekspresi budaya-agama yang mengganggu kerukunan. Pancasila menjadi penting dalam mengatasi konflik-konflik ini serta mendorong keberagaman dan dialog yang berkelanjutan.]